TINJAUAN STRATEGI PEMASARAN TABUNGAN TANDAMATA MY FIRST PADA BANK BJB KCP DARMAWANGSA - Dwi Utari (2023)
Awareness of saving at the bank is now starting to grow in children who aim to raise third-party funds, at BJB bank which launched consumer banking products in the form of average children's savings for under 17 years old. For bank bjb, it is a marketing concept that is community. To face competition in society in banking institutions, means of promotion or sale and profit or profit through consumers. This final project report uses qualitative descriptive methods and interviews, based on the interview process with the customer service department, bank Bjb has set the next steps to obtain the marketing goals of a company in the hope of creating mutual customer value and achieving mutually beneficial relationships. At the time of marketing implementation, there are several marketing strategies for Tandamata My First savings products in marketing Tandamata My First Bank savings products KCP Darmawangsa conducts marketing strategies through the concept of marketing mix based on 7 aspects, namely Product, Price, Place, Promotion, People, Process, Physical Evidence. Keywords: Tandamata My First Savings, Marketing Strategy